Perancangan Blind Flange Multi-Size pada Tube Bundle Heat Exchanger sebagai Alat Bantu Tes Hidrostatik - Ananda Maulana Rachmat Dhani; Mohammad M.Munir; Dhika A.Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
The hydrostatic testing process on tube bundle heat exchanger at PT. PAL Indonesia needs a tool called a blind flange. In this research object PT. PAL Indonesia produces 14 tube bundles with five different types. Each tube bundle type requires one pair of blind flanges, which will be placed on the fixed tube sheet, and a floating tube sheet for five pairs of blind flanges. This amount makes it difficult for the company to store and maintain blind flange products. Poor product maintenance will also impact the physical development, product function, and product life. This study aims to design a multi-size blind flange with a more functional design, ease of maintenance, and more economical manufacturing costs. This study refers to the flange design standards: ASME Section VIII Division 1 and the finite element method. The new concept produces static stress analysis, which has a safe value with a safety factor value of 3.868 and a von Misses stress of 115.2 MPa for fixed tube sheets. Meanwhile, the floating tube sheet produces a safety factor value of 3.676 and a von Misses stress of 122.4 MPa. The new concept costs Rp.488,510,757, which saves 17.18% of the cost of the existing product.